The effect of personalized health information on preventive behavior amongst risk groups: A randomized experiment in Pakistan during the COVID-19 pandemic - Lisa Rogge; Sheraz Ahmad Khan; Zohaib Khan; Muhammad Jawad Noon; Andreas Landmann; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2021)
Preventing infections is crucial for population groups that are at higher risk to experience a complicated disease course and have limited access to healthcare. Our research with lowincome households from Pakistan first documents gaps in knowledge and individual preventive practices in the context of the COVID-19 pandemic, despite pervasive public information campaigns. Second, using a randomized experiment, we evaluate whether a more targeted and personalized SMS information campaign exploiting administrative health records could contribute to narrowing this gap. We find that the intervention helped the at-risk population to adhere to higher levels of handwashing in the time between the first and second wave of infections, and all message recipients were more than twice as likely to use tele-medical services compared to the control group.
Keywords: 330; COVID-19; health insurance; information campaign; risk group behavior